(untitled) (Research, Society and Development, 2020)
The year 2020 is being marked by the pandemic of the new Coronavirus and its consequences for society. In the hospital environment, the pandemic has demanded from the local managers dedication to adapt the work processes to the new needs, being the best assistance to the patient with COVID-19 essential, without detriment to the safety of non-infected patients and health professionals. Objective: To describe the challenges of nursing management in oncology intensive care during the COVID-19 pandemic and to discuss the measures adopted to date to deal with the disease, in an exclusively oncology institution. Methodology: Descriptive study, with a qualitative approach, of the experience report type on the challenges and strategies adopted by the oncology nursing management in the intensive care unit (ICU) in face of the COVID-19 Pandemic in a reference hospital in oncology in Rio de Janeiro January. Results and discussion: seven thematic categories experienced during the adaptation of the service to the service to COVID-19 were identified: availability of beds, staff training, acquisition of equipment and supplies, organization of flows, reorganization of scale due to increased absenteeism, support to care professionals, deal with uncertainties. Conclusion: It is necessary to think about the dyad of care and safety for hospitalized patients and also for the professional who cares, considering the degree of transmissibility of Sars-Cov-2, still without effective medication, with its rapid clinical evolution that is difficult to control for all, and with increasing lethality in the epidemiological curve.